Welcome :: Homework Help and Answers :: Mathskey.com
Welcome to Mathskey.com Question & Answers Community. Ask any math/science homework question and receive answers from other members of the community.

13,434 questions

17,804 answers

1,438 comments

48,081 users

How do i solve this?

+2 votes

(x+3)(x-2)^2?

asked Feb 9, 2013 in PRE-ALGEBRA by skylar Apprentice

2 Answers

+2 votes

(x+3)(x-2)2

Mathematics formulas: (a-b)2=a2-2ab+b2

(x+3)(x2-2(x)(2)+22)

(x+3)(x2-4x+4)

FOIL method: the product of two binomials is the sum of the products of the First terms, the Outer terms, the Inner terms and the Last terms.

x(x2)+x(-4x)+x(4)+3(x2)+3(-4x)+3(4)

x3-4x2+4x+3x2-12x+12

x3-x2-8x+12

Therefore (x+3)(x-2)2 = x3-x2-8x+12.

answered Feb 11, 2013 by britally Apprentice
0 votes

Considering the linear equation as (x + 3)(x - 2)2 = 0.

Apply zero product property.

x + 3 = 0   and    (x - 2)2 = 0

⇒x = - 3   and    x = 2.

The solutions are x = - 3 and x = 2.

answered Jul 4, 2014 by lilly Expert

Related questions

...